1992
DOI: 10.1159/000109331
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin Stimulates the Secretion of [Met<sup>5</sup>]-Enkephalin and the Expression of Proenkephalin A mRNA in Bovine Adrenal Medullary Chromaffin Cells

Abstract: [Met5]-Enkephalin (ME) secretion and the expression of proenkephalin A (proENK) mRNA were studied following long-term exposure of bovine adrenal medullary chromaffin (BAMC) cells to pertussis toxin. Treatment with pertussis toxin for 24 h increased the secretion of ME in a concentration- and time-dependent manner. The magnitude of ME secretion continued to increase with time in the presence of pertussis toxin. The intracellular concentration of ME in the pertussis toxin-treated group was not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In most of these cases, the lack of inhibition can in retrospect be accounted for by the use of iso-H7, rather than authentic H7 (76,77), or very low concentrations of authentic H7 (78,79). In almost every study to date, authentic H7 used at concentrations between 50 and 100 M has been found to block gene induction.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these cases, the lack of inhibition can in retrospect be accounted for by the use of iso-H7, rather than authentic H7 (76,77), or very low concentrations of authentic H7 (78,79). In almost every study to date, authentic H7 used at concentrations between 50 and 100 M has been found to block gene induction.…”
Section: Discussionmentioning
confidence: 99%
“…The release of AM and PAMP by dbcAMP occurs along the same lines as the release of methionine‐enkephalin and catecholamines evoked by 8‐Br‐cAMP, another membrane permeable analogue of cAMP, or by forskolin, an activator of adenylyl cyclase [32–34]. In addition, changes in ir‐AM, ir‐PAMP and chromogranin B by dbcAMP were attenuated by H89, strongly suggesting that the cAMP‐dependent protein kinase pathway is involved in the gradual release of these peptides from chromaffin granules.…”
Section: Discussionmentioning
confidence: 97%
“…Adrenal medulla and pheochromocytoma contain various biologically active peptides other than AM and PAMP, the synthesis of which is regulated by various intracellular signals. The regulation of AM and PAMP, as well as that of the corresponding mRNA, seem to be unique in comparison with other peptides because elevation of cAMP increased the expression of mRNAs encoding the soluble proteins enkephalin [33,34], chromogranin B, neuropeptide Y and a neuroendocrine‐specific gene product, VGF [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the treatment of chromaffin cells with 12-O-tetradecanoylphorbol 13-acetate (a PKC activator), forskolin (an adenyl cyclase activator), or 8-bromo-cyclic AMP (a cyclic AMP analogue) increases the secretion of ME as well as the expression of proENK mRNA (Eiden et al ., 1984 ;Quach et al ., 1984 ;Inturrisi et al ., 1988 ;Kley, 1988 ;Farin et al ., 1990 ;Sub et al ., 1993) . In addition, treatments with calcium channel blockers or a calmodulin antagonist effectively inhibit the increases of both ME secretion and the expression of the proENK gene (Kley et al ., 1987 ;Stachowiak et al ., 1991 ;Suh et al, 1992aSuh et al, , 1993 . Our studies as well as those from other laboratories have demonstrated that third messengers such as AP-1 transcription factors play a role in the regulation of the proENK gene (Sonnenberg et al ., 1989 ;Mar et al ., 1992 ;Suh et al, 1993) .…”
Section: Introductionmentioning
confidence: 99%